2009
DOI: 10.1021/ic901305g
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Synthesis: The Fascinating and Diverse Chemistry of Polar Intermetallic Phases†This article is based on J. D. Corbett’s address upon receipt of the 2008 American Chemical Society’s F. Albert Cotton Award in Synthetic Inorganic Chemistry sponsored by the F. Albert Cotton Endowment Fund.

Abstract: Exploratory synthetic adventures regarding the inorganic chemistry of polar intermetallic phases have proven to be especially productive of novel compositions, new and unprecedented structures, and unusual bonding regimes. Reactions of diverse elements with widely different electronegativities allow the definition of two opposed classes of products: polycationic or polyanionic clusters or networks of metals paired with the corresponding monatomic anions or cations. These can be usefully viewed as intermetallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Sc 6 PdTe 2 , CaBe 2 Ge 2 ). 64,65 Perhaps less appreciated are the layered structures with electronegative spacers. Examples such as ClCa 2 N and I 3 La 5 Si 5 have halogen spacers and polycationic slabs.…”
Section: A Distribution Of Identified Spacer Elementsmentioning
confidence: 99%
“…Sc 6 PdTe 2 , CaBe 2 Ge 2 ). 64,65 Perhaps less appreciated are the layered structures with electronegative spacers. Examples such as ClCa 2 N and I 3 La 5 Si 5 have halogen spacers and polycationic slabs.…”
Section: A Distribution Of Identified Spacer Elementsmentioning
confidence: 99%
“…In fact, examining the electronic structures of (active-metal) transition-metal tellurides (active-metal = group I and III elements) revealed that the bonding nature in these tellurides is dominated by strong transition-metal−tellurium interactions beside minor transition-metal−transition-metal or tellurium−tellurium interactions. Because the transition-metal−tellurium interactions in these tellurides exhibited attributes of strong mixed-metal bonds, it was concluded that these tellurides should be assigned to the groups of polar intermetallics [19,20] rather than the Zintl phases.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, certain concepts, e.g., those stated by Hume-Rothery [6][7][8] or Zintl and Klemm [9][10][11], help to understand the distributions of valence-electrons in some intermetallics. On the other hand, more recent research [1,12] on polar intermetallic compounds revealed the existence of polyanionic or polycationic units ("clusters") which are combined with monoatomic counterions, but are electron-poorer relative to Zintl phases.…”
Section: Introductionmentioning
confidence: 99%